Exploring Organized Interests in Post-Communist Policy-Making The "Missing Link" - Dobbins, Michael; Riedel, Rafał (Routledge Research in Comparative Politics, 2021)
This book examines organized interests in post-communist Central and Eastern Europe (CEE), providing incisive analyses in three critically important policy areas - healthcare, higher education and energy. The four countries surveyed - Poland, Hungary, Slovenia and the Czech Republic - afford rich diversity offering broad empirical material available for cross-country and cross-policy comparative analyses. Featuring interdisciplinary research, the book draws together recent developments in the evolution of post-communist advocacy organizations, their population ecology dynamics, interest intermediation, the influence of organized interests and their (bottom-up and top-down) Europeanization. This book will be of key interest to scholars and students of Central and Eastern European politics, interest groups and lobbying, post-communism, transition and consolidation studies, and more broadly to European studies/politics.